1997
DOI: 10.1111/j.1399-0004.1997.tb02476.x
|View full text |Cite
|
Sign up to set email alerts
|

MN blood group affects response of serum LDL cholesterol level to a low fat diet

Abstract: Previous studies found that MZ twin pairs who are blood group NN have greater intrapair variability in plasma lipid levels than those who are MM or MN. This led to the prediction that the response of plasma lipid levels to a low fat diet would depend on MN blood group, the greatest response being in those who are NN. The present study was based upon 254 patients who took part in the Australian Polyp Prevention Project. This was a 2 × 2 × 2 randomised factorial design based upon the presence or absence of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Participants in a dietary intervention program with homozygous MM and NN genotypes (47%) had similar responses to a low‐fat diet, which resulted in almost all of the reported reduction in LDL cholesterol; in contrast, those with the heterozygous MN genotype (53%) had little or no response to the low‐fat diet . This finding is relevant when prescribing a low‐fat diet for LDL cholesterol management because it indicates that about half of the general population at large would have a similar response to a low‐fat diet …”
Section: Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…Participants in a dietary intervention program with homozygous MM and NN genotypes (47%) had similar responses to a low‐fat diet, which resulted in almost all of the reported reduction in LDL cholesterol; in contrast, those with the heterozygous MN genotype (53%) had little or no response to the low‐fat diet . This finding is relevant when prescribing a low‐fat diet for LDL cholesterol management because it indicates that about half of the general population at large would have a similar response to a low‐fat diet …”
Section: Cancermentioning
confidence: 95%
“…Studies since the early 1980s have investigated the genetic basis for differences in LDL cholesterol, HDL cholesterol, and triglycerides, and several have found an association between the MN blood group and LDL cholesterol levels . Participants in a dietary intervention program with homozygous MM and NN genotypes (47%) had similar responses to a low‐fat diet, which resulted in almost all of the reported reduction in LDL cholesterol; in contrast, those with the heterozygous MN genotype (53%) had little or no response to the low‐fat diet .…”
Section: Cancermentioning
confidence: 99%
“…In this study, it was found that M+ accounted for 75.2% and N+ for 73.0%, which was lower in the former and higher in the latter than in the study of Halawani et al [25]. Early studies have found that MN blood group is related to plasma lipid level [26] and essential arterial hypertension in young adults [27], but whether it is related to COVID-19 infection is still unknown. Fortunately, we found that MN blood group was associated with susceptibility to COVID-19, although the reason is unknown.…”
Section: Plos Onementioning
confidence: 47%